2011
DOI: 10.1177/0255761411408505
|View full text |Cite
|
Sign up to set email alerts
|

Piano playing reduces stress more than other creative art activities

Abstract: Few studies have been conducted on the physiological effects of creative art activities. In this study, the effects of creative art activities on human stress were investigated, and their effects were compared in 57 healthy college students (27 males and 30 females). Subjects were divided into four groups, each of which participated in 30-minute sessions of one of the following creative activities or a control activity: (1) playing the piano; (2) molding a piece of clay; (3) calligraphy (writing using a brush … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
2
15
0
1
Order By: Relevance
“…This result is consistent with results of Toyoshima et al. (), whose study of college students provided evidence of cortisol benefits associated with clay molding and calligraphy as well as piano playing. Although different visual arts activities may be associated differently with emotional change (e.g., Drake & Winner, ), the present results attest to the potential for the visual arts to predict reduced cortisol for children facing poverty risks.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result is consistent with results of Toyoshima et al. (), whose study of college students provided evidence of cortisol benefits associated with clay molding and calligraphy as well as piano playing. Although different visual arts activities may be associated differently with emotional change (e.g., Drake & Winner, ), the present results attest to the potential for the visual arts to predict reduced cortisol for children facing poverty risks.…”
Section: Discussionsupporting
confidence: 93%
“…In examining the impact of music, specifically, we found lower average cortisol after music compared to homeroom classes. This result is consistent with studies showing lower cortisol after music listening (e.g., Khalfa et al., ) and piano playing (Toyoshima et al., ) for heterogeneous income samples of adults. Although some kinds of music, for example, in video games, might lead to cortisol elevations (Hébert, Béland, Dionne‐Fournelle, Crête, & Lupien, ), the present research adds to evidence that music can be used to lower cortisol.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Table 1 summarizes content, sample, and intervention characteristics, design, research methods, and results of the studies identified [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. In total, 37 studies met our inclusion criteria, 11 studies (29.7%) investigated the effect of AT or art interventions on stress, 20 studies (54.1%) focused on MT or musical interventions, and 6 studies (16.2%) assessed the effects of DMT or dance interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Two of the studies [ 45 , 50 ] used physical measures (cortisol level [ 45 ]; pulse and blood pressure [ 50 ]) to operationalize stress. MT or musical interventions reduced stress and anxiety in 16 of 20 studies (10 on MT, 6 on music interventions) [ 53 , 54 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 65 , 66 , 67 , 68 , 70 , 72 ]. Four studies (one of MT, three on music interventions) [ 53 , 61 , 68 , 70 ] reported reductions in cortisol level, as a physical measurement of stress, and two studies (both on MT) [ 53 , 58 ] found a decrease of sleeping problems through musical interventions.…”
Section: Resultsmentioning
confidence: 99%